Effect of cholesterol and fat supplemented diets on cholesterol contents of follicular fluid and egg yolk of quails of three age groups - VERMA, NIRUPAMA D; PANDA, J N; SINGH, K B; MOUDGAL, R P (The Indian Journal of Animal Sciences, 2013)
Effect of feeding cholesterol and fat supplemented diets was studied on cholesterol contents of follicular yolk and egg yolk of quails of 3 different age groups i.e. 5-week-old, 12-week-old and 1-year-old. Five different dietary combinations were fed to different groups for 30 days. The diets were : control diet, normal diet without fish-meal, control diet with 1% cholesteral, control diet with 10% lard, and control diet with 1% cholesterol and 10% lard. Different dietary treatments affected both the follicular and egg yolk cholesterol levels in all the treated birds. The cholesterol levels were higher in i-year-old birds irrespective of the dietary treatments. The dietary treatment affected the cholesterol level of F1 follicular yolk of 12-week-old the least as compared to 5-weeks old or 1-yearold laying quails.